Genetic Diversity in Tomato (Solanum lycopersicum L.) based on Quantitative Traits - Bhandari, H. R.; Srivastava, K.; Shreya, (International Journal of Bio-resource and Stress Management, 2022)
Present investigation was conducted at Institute of Agricultural Sciences, Banaras Hindu University (BHU), Varanasi, Uttar Pradesh state, India during 2014−15 to assess the genetic diversity among 66 accessions of tomato maintained at Institute of Agricultural Sciences, Banaras Hindu University. The techniques of principal component analysis and D2 analysis were used for genetic diversity assessment. The analysis revealed significance of four principal components representing 70.12% of the total variability. Some of the important yield traits like average fruit weight, fruit yield plant-1 and number of locules fruit-1 were the most important traits in PC1 indicating that selection for diversity must be based on these traits. The correlation plot depicted that the traits plant height, number of fruits cluster-1 and number of fruits plant-1 were closely related to each other. Based on the scores of 1st and 2nd principal component, the genotypes were distributed in biplot. Most of the genotypes were congregated near the centre and revealed narrow genetic diversity existing among the germplasm accessions. The coordinates of the genotype EC 538380 indicated it as the most unique. The entries EC 538155, Pant T3, EC 521069, EC 538434 and EC 168283 were standing separate from the majority of entries. Cluster analysis also indicated congregation of most of the genotypes in one group. Overall, the study indicated limited genetic diversity in the test material.